Arabidopsis TIC236 contributes to proplastid development and chloroplast biogenesis during embryogenesis - Liu, Mei; Chen, Lifen; Gu, Shijie; Zhang, Aiwei; Tong, Mengjuan; Wang, Shuailei; Wang, Juntao; Zhu, Yirui; Zhang, Jingsheng; Sun, Yu; Guo, Yi; Li, Rui (Frontiers in Plant Science, 2024)
Plastids are essential, semi-autonomous organelles in plants that carry out a multitude of functions during development. Plastids existing in different subtypes are derived from proplastids progenitors and interconvert in response to environmental and growth cues. Most efforts focus on the differentiation from proplastid to other forms. However, the studies of proplastid development are insufficient and whether proplastid biogenesis affects plant growth is yet to be determined. Arabidopsis TIC236, a translocon component at the inner membrane of the chloroplast envelope, is critical for importing chloroplasttargeted preproteins and chloroplast division. In this study, we uncovered the fundamental influence of proplastid biogenesis on embryo development by exploring the function of TIC236 during embryogenesis. Widespread and strong expression of TIC236 was observed in leaves and embryos. The null mutant tic236 had an embryo-lethal phenotype, with cell division in the mutant embryos delayed starting at the octant stage and arrested at the globular stage.Transmission electron microscopy revealed enlarged proplastids with an aberrant inner structure at the dermatogen and globular stages that ultimately did not differentiate into chloroplasts. Additionally, the fluorescence signal distribution patterns of tic236 embryos carrying the pDR5rev::3xVENUS-N7, pPIN1::PIN1-GFP, pWOX5::GFP, and pSCR::H2B-YFP reporter systems were altered. Together, we provide genetic evidence supporting proplastid biogenesis plays a vital role in embryo development and TIC236 is identified as an indispensable player, ensuring normal proplastid development.